EFFECTS OF SOCIAL MEDIA IN CRIME PREVENTION EFFORTS OF QCPD - POLICE STATION 4 IN BARANGAY STA. MONICA QUEZON CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
In today’s digital era, social media platforms have become integral to everyday life, offering dynamic tools for communication, information sharing, and public engagement. These platforms have also emerged as potential instruments in crime prevention, allowing law enforcement agencies to reach communities more effectively and foster collaboration in maintaining public safety. This study explores the role of social media in the crime prevention efforts of the Quezon City Police District – Police Station 4 (QCPD-PS4), particularly in Barangay Sta. Monica. This research utilized a descriptive method and employed snowball sampling to gather data from 50 Criminal Justice Officers of QCPD–PS4. The study aimed to assess the effectiveness of social media in terms of crime awareness, the adoption of security precautionary measures, and suspect identification. Data collection was conducted through direct distribution and retrieval of survey questionnaires, ensuring timely and complete responses. The study also sought to identify challenges associated with social media use in crime prevention and propose actionable solutions to enhance its impact. The findings revealed that most respondents were male patrol officers between the ages of 26 and 33. Overall, the respondents agreed that social media positively contributes to crime prevention, particularly by increasing public awareness of crime incidents, promoting safety measures, and aiding in the identification of suspects. However, concerns were raised regarding misinformation and its consequences, including the spread of false information, unnecessary fear, poor decision-making, and wrongful accusations. The most pressing challenge cited was the risk posed by online harassment and cyber threats, which discourage victims from reporting crimes. The most recommended action was implementing stricter fact-checking mechanisms to reduce misinformation and the spread of fake news. To address these issues, the study proposed an action plan focusing on enhancing digital security and responsible use of social media. Key recommendations include strengthening fact-checking mechanisms, conducting digital literacy programs to educate the public, and creating secure, encrypted online reporting channels to protect informants. Expanding internet access in underserved areas and improving the monitoring of cyber threats were also suggested. Furthermore, the study advocates for regular training of law enforcement personnel on digital crime prevention, community engagement through social media campaigns, and collaboration with technology experts to design secure reporting systems. These strategies aim to improve the effectiveness of social media as a tool for crime prevention in Barangay Sta. Monica and beyond.
Keywords: social media and crime prevention; digital literacy; misinformation; online crime reporting; cybersecurity; community policing; law enforcement technology